Indirect reference intervals for haematological parameters in capillary blood of pre-school children - Zeljkovic, Aleksandra (Array, 2021)
Introduction: Indirect estimation of reference intervals (RIs) is straightforward and inexpensive procedure for determination of intra-laboratoryRIs. We applied the indirect approach to assess RIs for haematological parameters in capillary blood of pre-school children, using results stored inour laboratory database.Materials and methods: We extracted data from laboratory information system, for the results obtained by automatic haematology analyser incapillary blood of 154 boys and 146 girls during pre-school medical examination. Data distribution was tested, and logarithmic transformation wasapplied if needed. Reference intervals were calculated by the nonparametric percentile method.Results: Reference intervals were calculated for: RBC count (4.2-5.4 x1012/L), haemoglobin (114-146 g/L), MCH (25.0-29.4 pg), MCHC (321-368 g/L),RDW-SD (36.1-43.5 fL), WBC count (4.5-12.3 x109/L), neutrophils count (1.7-6.9 x109/L) and percentage (29.0-69.0%), lymphocytes count (1.6-4.4x109/L) and percentage (21.9-60.7%), PLT (165-459 x109/L), MPV (8.1-11.4 fL) and PDW (9.2-14.4%). Gender specific RIs were calculated for monocytescount (male (M): 0.2-1.6 x109/L; female (F): 0.1-1.4 x109/L) and percentage (M: 2.5-18.3%; F: 1.8-16.7%), haematocrit (M: 0.34-0.42 L/L; F:0.34-0.43 L/L), MCV (M: 73.4-84.6 fL; F: 75.5-84.2 fL) and RDW (M: 12.1-14.3%; F: 11.7-13.9%), due to observed gender differences in these parameters(P = 0.031, 0.028, 0.020, 0.012 and 0.001; respectively). Estimated RIs markedly varied from the literature based RIs that are used in the laboratory.Conclusions: Indirect method employed in this study enables straightforward assessment of RIs in pre-school children. Herein derived RIs differedfrom the literature-based ones, indicating the need for intra-laboratory determination of RIs for specific populations and sample types.